Endovascular aneurysm repair: current status on device specifications and outcomes - Cordeiro,Filipa (2018)
Introduction: Since its first introduction in 1991, endovascular aneurysm repair (EVAR) became the preferred modality for abdominal aortic aneurysms (AAA) repair. Several devices have been launched over the years addressing progressively more complex anatomies. The aim of this review is to provide an update on current endografts and compare their results. Methods: MEDLINE databases were searched for endografts features and respective outcomes. Results: Currently, a significant variety of grafts is approved for clinical use, targeting different anatomic properties. There are presently six CE and FDA approved devices: Zenith®, AFX®, C3 EXCLUDER®, Endurant® II, Ovation® and Aorfix™; while six more have only the CE mark: Anaconda™, E-vita ABDOMINAL XT®, E-tegra®, Incraft®, TREOVANCE® and Altura™. Also, there are four fenestrated and branched endografts available for treating thoracoabdominal aneurysms: Zenith® Fenestrated, Fenestrated Anaconda™, Zenith® p-Branch® and Zenith® t-Branch®. The Endurant II and Treovance stent grafts can accommodate neck lengths ≥10 mm; Aorfix and Anaconda are more liberal regarding neck angulation, extending of infrarenal neck angulation up to 90º. Finally, Zenith, C3 Excluder, Ovation and Incraft stent grafts can be used with distal fixation length ≥10 mm. Conclusion: New-generation endografts perform better than the older ones, especially in challenging anatomies. Mid-term outcomes between contemporary stent-grafts seem to be similar for most of the outcomes. However, no randomized controlled trials exist comparing different contemporary stent grafts, making conclusions difficult to accomplish. Long-term follow-up reviews are required to assertively take assumptions about different stent grafts performance.